Porphyrinic-nanoplatforms: controlled intracellular generation of reactive oxygen species in human mesenchymal stem cells - Lavado, Andrea Sofia Caetano das Neves (2014)
Reactive Oxygen Species (ROS) are known as important intracellular signaling molecules. These are also well known for their role in oxidative stress and cellular damage, leading to their involvement in several pathologies. Despite the widespread postulation of ROS mechanisms, little is actually known about the immediate response in living cells to the generation of these highly reactive compounds. The development of nanoplatforms incorporating photosensitizers would permit the generation of ROS at specific sub-cellular locations and determine the in situ cellular response.